A RESPONSE TO BUSHMAN, NOLL, AND GREGORY. - Kuklick, Bruce (Fides et historia, 2011)
The author reflects on the role of religious belief in the writing of history. His article responds to the essays "Mormon History Inside Out" by Richard Lyman Bushman, "Historians’ Metaphysical Beliefs and the Writing of Confessional Histories" by Brad S. Gregory, and "Coming to Terms as a Christian Historian with F. H. Bradley" by Mark A. Noll. It is suggested that historians with religious beliefs may provide readers with an empathetic understanding of historical religious communities, they are not in a unique position to provide this insight. According to the author, the fact that historians have no way of evaluating supernatural causes for historical events precludes their serious consideration in the practice of critical history.